Low Cost Robots as Target System for Students Training Using Java - Samuelsen, Dag Andreas Hals; Graven, Olaf Hallan (International Journal of Online and Biomedical Engineering (iJOE), 2009)
The topic of this paper is a cost efficient programming environment designed with a focus on enhancing the studentsâ?? engagement and effort to complete the assignments. The environment is designed to give the students an approach that is similar to a professional work situation with respect to hardware-software interaction, documentation and complexity. The system presented is based on low-cost, off-the-shelf equipment for easy implementation on mass in an educational institution. As part of the system a low-cost positioning system for mobile robots in an indoor application is included, giving further opportunities for engaging task for the students.